KOMPAK: The Program to Improve Quality of Life for Parents of Childhood Cancer Patients - Siti Nur Fauziyah Hukdar; Eva Meizara Puspita Dewi (PT ARRUS Intelektual Indonesia, 2023)
Parents of Childhood Cancer patients as caregivers have an impact on the many tasks that must be undertaken and cause stress, causing physical and psychological burdens. As a caregiver, this is closely related to the increase in parenting stress which can lead to a decrease in the quality of life of the patient's parents. This study aims to determine the effectiveness of the intervention program